Design of multilayer cauliflower-like structure SiO2/SiC–Y2Si2O7 composite ceramics as high-efficiency electromagnetic wave absorbers. Issue 22 (15th November 2022) - Wei, Hanjun; Liu, Jie; Feng, Pei; Yang, Shenquan; Xue, Jimei; Wang, Cunxian; Zhao, Feng; Wang, Qingyuan
Abstract: A reasonable design of the microstructure and phase composition of rare earth silicate composites can enhance their corrosion resistance and their electromagnetic (EM) properties. However, individual rare earth silicates cannot fulfill the requisites for novel EM absorption materials. Herein, we introduce SiC and SiO2 to establish novel SiO2 /SiC–Y2 Si2 O7 composite ceramics with a multilayer cauliflower-like structure using sol-gel, pressure-free sintering, chemical vapor infiltration (CVI) and oxidation at 1100 °C (1.5 h). SiC increases the relative complex permittivity and attenuation capabilities and the SiO2 layer impedance matching mediator effectively balances the impedance matching properties. The SiO2 /SiC–Y2 Si2 O7 composite ceramics, therefore, exhibit superior EM wave absorption properties: the reflection coefficient minimum (RCmin ) is −21.5 dB, with a 3.65 mm thick covering, in the whole X band (4.2 GHz). This is due to the impedance matching, polarization loss, conductivity loss, and internal multiple reflections loss. In brief, this work provides a strategy for achieving the EM stealth characteristics of rare earth silicate materials.